ARAH BARU PENGEMBANGAN ULUMUL QUR’AN: TELAAH METODOLOGIS ILMU ASBABUN NUZUL - munawir, munawir; Musta?in, Musta?in (At-Tibyan: Jurnal Ilmu Alqur`an dan Tafsir, 2020)
In its corridor as a science, the science of asbabun nuzul is on a par with other scholars. Even though it was constructed by scholars, it did not necessarily make it immune to criticism and immune to development; there are always areas that are unthinkable and not even thought of. This is the focus of this article's discussion. Through qualitative-interpretative methods and philosophical approaches (philosophical approaches), critical approaches (critical approaches), and constructivist approaches, the results are obtained that the areas that have not been and are not even thought of at the same time as the development of contemporary asbabun nuzul science is the formulation of macro asbabun nuzul theory, and the formulation the rules of al-ibratu bil maqashidi